OXYGEN ISOTOPIC COMPOSITION AND NATURE OF FLUID DURING THE FORMATION OF HIGH-Al CORUNDUM-BEARING ROCKS OF MT. DYADINA, NORTHERN KARELIA - Krylov D.P.; Glebovitsky V.A. (My University, 2007)
The Al-oversaturated corundum-bearing rocks of high-grade complexes are characterized by unusual chemical composition (high contents of Al and Mg at relatively low Si contents), unique mineral assemblages (sapphirine, hogbömite, spinel, gedrite, and others), but their origin remains unclear at present. The main hypothesis is that they were formed through metasomatism of the host rocks under the influence of fluid filtration. The origin of the protolith and the role of fluids in the transportation of matter and transformation of mineral assemblages are the most important problems in the genesis of corundum-bearing rocks. In this paper, the high-Al mineral assemblages were studied using oxygen isotopy. The target objects are corundum-bearing assemblages of Mt. Dyadina (northern Karelia), the host rocks of the Chupa nappe, and magmatic rocks at the contact with high-Al sequences.